Cell ingression: Relevance to limb development and for adaptive evolution. Issue 1 (27th December 2017) - Pasiliao, Clarissa C.; Hopyan, Sevan
Summary: Cell ingression is an out‐of‐plane type of cell intercalation that is essential for the formation of multiple embryonic structures including the limbs. In particular, cell ingression underlies epithelial‐to‐mesenchymal transition of lateral plate cells to initiate limb bud growth, delamination of neural crest cells to generate peripheral nerve sheaths, and emigration of myoblasts from somites to assemble muscles. Individual cells that ingress undergo apical constriction to generate bottle shaped cells, diminish adhesion to their epithelial cell neighbors, and generate protrusive blebs that likely facilitate their ingression into a subepithelial tissue layer. How signaling pathways regulate the progression of delamination is important for understanding numerous developmental events. In this review, we focus on cellular and molecular mechanisms that drive cell ingression and draw comparisons between different morphogenetic contexts in various model organisms. We speculate that cell behaviors that facilitated tissue invagination among diploblasts subsequently drove individual cell ingression and epithelial‐to‐mesenchymal transition. Future insights that link signalling pathways to biophysical mechanisms will likely advance our comprehension of this phenomenon.